2011
DOI: 10.1007/s11431-010-4204-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of steel slag on the hydration of cement during the hydration process of complex binder

Abstract: The influence of steel slag, a by-product from the processing of iron to steel, on the hydration of cement during the hydration process of complex binder was studied by calorimetry, X-ray diffraction analysis, and Ca(OH) 2 content determination. The results show that steel slag and cement affect each other's hydration by changing the hydration environment. Steel slag does not react with the hydration products of cement. The dormant period of cement-steel slag complex binder during the hydration is longer than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(56 citation statements)
references
References 24 publications
3
52
0
1
Order By: Relevance
“…However, as the hydration age increased, the gap between pure cement mortar and blended cement mortars became smaller. This is because the cementitious part of steel slag makes a great contribution to the strength of blended cement mortars and steel slag can promote the hydration degree of cement at later ages [20].…”
Section: Water Requirement Of Normal Consistency Setting Time and Smentioning
confidence: 99%
“…However, as the hydration age increased, the gap between pure cement mortar and blended cement mortars became smaller. This is because the cementitious part of steel slag makes a great contribution to the strength of blended cement mortars and steel slag can promote the hydration degree of cement at later ages [20].…”
Section: Water Requirement Of Normal Consistency Setting Time and Smentioning
confidence: 99%
“…Krstulovic [6] reported that the hydration reaction process of cement-based materials consists of three stages, namely nucleation and crystal growth (NG), interactions at phase boundaries (I) and diffusion (D). By using the Krstulovic-Dasic model, Yan Peiyu [7][8][9], Wang Qiang et al [10][11][12][13][14] discussed the hydration rate of cementGGBSsteel slagprobed into the hydration kinetics of cementbased cementitious materials, and revealed that the reaction process simulated by the Krstulovic-Basic model [6] is consistent with the actual reaction process.…”
Section: Introductionmentioning
confidence: 99%
“…Tsakiridis et al [8] studied the utilization of steel slag for Portland cement clinker production and pointed out that the addition of steel slag by 10.5% in the raw meal did not affect the hydration process during Portland cement production. Wang et al [10] found that the dormant period of blended cement containing steel slag is longer than that of Portland cement. Monshi and Asgarani [11] found that blending 10% extra iron slag to a cement composed of 49% iron slag, 43% calcined lime and 8% steel slag kept the compressive strength of concrete for type I Portland cement.…”
Section: Introductionmentioning
confidence: 99%